Analisis Peran Kepemimpinan Transformasional dalam Memediasi Konflik Interpersonal pada Organisasi Karang Taruna - Muttaqin, Izzul; Dewi, Karina Setyo; Agustina, Latifah (JURNAL STIE SEMARANG, 2024)
This article discusses the application of transformational leadership in mediating interpersonal conflicts in the Karang Taruna organizational environment. Using a qualitative descriptive approach with data collection instruments, namely open interviews and non-participant observation, this research explores how elements of transformational leadership, including inspiration, motivation and involvement, play a crucial role in shaping the dynamics of relationships between members and leaders to achieve common goals. The results show that transformational leadership is not only a mediator of conflict, but also an agent of change that can turn conflict into opportunities for growth and learning. Leaders who successfully implement this approach enable open communication, build trust, and encourage productive collaboration. In this research, the Karang Taruna organizational context presents a comprehensive picture of transformational leadership practices. Practical implications of these findings include improving conflict management, increasing organizational member satisfaction, and creating an environment that supports individual and group growth. This study not only provides a strong theoretical foundation, but also provides practical insights that can help leaders and managers improve their leadership effectiveness in managing interpersonal conflict. The conclusion of this article provides a valuable contribution to the development of transformational leadership practices to mediate interpersonal conflicts in the Karang Taruna organization and similar organizations.